2019
DOI: 10.48550/arxiv.1909.10660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring Graph Neural Networks for Stock Market Predictions with Rolling Window Analysis

Daiki Matsunaga,
Toyotaro Suzumura,
Toshihiro Takahashi

Abstract: Recently, there has been a surge of interest in the use of machine learning to help aid in the accurate predictions of financial markets. Despite the exciting advances in this cross-section of finance and AI, many of the current approaches are limited to using technical analysis to capture historical trends of each stock price and thus limited to certain experimental setups to obtain good prediction results. On * Equal contribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…• TGCN [25]: TGCN leverages a variant of graph convolutional networks [17] to propagate the historical price information on the stock graph for stock trend forecasting. It only uses historical price data and does not use the event information.…”
Section: Compared Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• TGCN [25]: TGCN leverages a variant of graph convolutional networks [17] to propagate the historical price information on the stock graph for stock trend forecasting. It only uses historical price data and does not use the event information.…”
Section: Compared Methodsmentioning
confidence: 99%
“…Specifically, [44] proposed a new State Frequency Memory (SFM) recurrent network to discover the multi-frequency trading patterns for stock price movement prediction; [18] presented a multi-task recurrent neural network with high-order Markov random fields (MRFs) to predict stock price movement direction; [11] leveraged adversarial training to simulate the stochasticity during model training. Besides, to improve the performance of technical analysis, some recent efforts [6,12,16,25] leveraged Graph Neural Networks [17,38] to capture the relationships between different stocks.…”
Section: Technical Analysismentioning
confidence: 99%
“…Cross-stock Methods. To mine the cross-stock shared information and improve the stock trend forecasting performance, many cross-stock methods [6,13,17,27] leveraged the Graph Neural Networks [19,39] to capture the relationships between different stocks. The [6] and [13] utilize the graph convolutional networks (GCN) to capture the stocks' shareholder relations and industry relations, respectively.…”
Section: Technical Analysismentioning
confidence: 99%
“…For example, some straightforward methods [33] directly used the predefined stock concepts as input features of the linear forecasting model. In addition, some others [13,17,23,27] used the same predefined concepts to form up relations between two stocks and leveraged the Graph Neural Network (GNN), whose edges are defined by conceptual relations, to build a more accurate stock trend forecasting model. While these recent studies have revealed the potential of stock concepts in boosting stock trend forecasting, they are still enduring some limitations that restrain them from fully leveraging the value of stock concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Graph neural networks (GNNs) have recently emerged as one the most popular machine learning models for processing and analyzing graph-structured data [1,2]. GNNs have gained significant and steady attention due to their extraordinary success in solving many challenging tasks in a variety of scientific disciplines such as computational pharmacology [3], molecular chemistry [4], physics [5], finance [6,7], wireless communications [8], and combinatorial optimization [9], to name a few.…”
Section: Introductionmentioning
confidence: 99%